2014
DOI: 10.1111/nyas.12379
|View full text |Cite
|
Sign up to set email alerts
|

Design of intrahepatocyte copper(I) chelators as drug candidates for Wilson's disease

Abstract: Wilson's disease is an autosomal recessive disease caused by mutations on the ATP7B gene found on chromosome 13. Since the corresponding ATPase is in charge of copper (Cu) distribution and excretion in the liver, its malfunctioning leads to Cu overload. This short review deals with treatments of this rare disease, which aim at decreasing Cu toxicity and are, therefore, based on chelation therapy. The drugs used since the 1950s are described first, then a novel approach developed in our laboratory is presented.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…This strategy for chelating intracellular copper is expected to avoid systemic toxicity caused by excessive release of copper from the liver and thus, maintaining free copper plasma in the safe range. One example of this concept is a novel chelator that is a tripodal cysteine-based ligand inspired by metallothioneins 85,86. Its high affinity to the liver has been achieved with specific recognition elements of the asialoglycoprotein receptor that is specific for targeting hepatocytes.…”
Section: Treatment Of Wdmentioning
confidence: 99%
“…This strategy for chelating intracellular copper is expected to avoid systemic toxicity caused by excessive release of copper from the liver and thus, maintaining free copper plasma in the safe range. One example of this concept is a novel chelator that is a tripodal cysteine-based ligand inspired by metallothioneins 85,86. Its high affinity to the liver has been achieved with specific recognition elements of the asialoglycoprotein receptor that is specific for targeting hepatocytes.…”
Section: Treatment Of Wdmentioning
confidence: 99%
“…However, some side effects related to this therapy have been reported. 14 More precisely, it has been shown that D-Pen can contribute to increase the neurologic deterioration expressed by some Wilson's disease patients, which may be due to a lack of specificity of the drug.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In the biomedical community, Ybt was recently recognized for a parallel ability to bind and sequester copper (23,24). The potential to selectively bind copper also holds promise in treating Wilson's disease, in which an excess of this metal accumulates in tissue (25)(26)(27). These and other situations will benefit from the recombinant capabilities that accompany the production of Ybt, and likely future siderophore products, when genetically tractable heterologous hosts such as E. coli are used.…”
mentioning
confidence: 99%